Assessment of radiological parameters of soil in Kogi State, Nigeria. Issue 1 (2nd January 2017) - Usikalu, M. R.; Fuwape, I. A.; Jatto, S. S.; Awe, O. F.; Rabiu, A. B.; Achuka, J. A.
ABSTRACT: The natural radioactivity levels of soil samples collected from four local government areas in Kogi State, Nigeria were measured using a hyper-pure germanium detector, and the radiological hazard parameters associated with them were estimated. The measured concentration ranged from 7.82 ± 0.63 to 82.22 ± 1.99 Bq kg −1 for 238 U, 11.05 ± 1.10 to 114.86 ± 4.72 Bq kg −1 for 232 Th, and 3.38 ± 0.50 to 1272.20 ± 23.36 Bq kg −1 for 40 K. Omala local government was found to have the highest concentrations of 238 U (44.31 Bq kg −1 ) and 232 Th (52.13 Bq kg −1 ), while Ajaokuta has the highest concentration of 40 K (711.72 Bq kg −1 ). The lowest activity concentrations of 238 U and 232 Th were measured from soil samples collected from Ankpa local government area and 40 K from Dekina local government area. It was noted that the activity concentrations of 40 K were generally low for all the areas investigated except for Ajaokuta areas. The radium equivalents calculated for all the locations were observed to be lower than the radiation protection regulatory body reference value of 370 Bq kg −1 . The radiological parameters estimated for most of the locations compared well with world average values, except for Odogba-okaba, Salem University, Forest, Nepa, Gerugu, Niger Bridge, Igaliwu, Ijeke-ogane, Bagana, and Abegikolo villages, whose values exceeded the recommended limit. This may suggest that those living or working in these areas may be exposed to higher radiation burden from the natural radionuclides.